Effects of gonadotropin on oestrus and reproductive indicators of delayed oestrus common palm civets (Paradoxurus hermaphroditus) - Thu Hiền, Nguyễn Thi; Phương Thảo, Nguyễn Thị; Bình, Nguyễn Thanh (Hue University Journal of Science: Natural Science, 2020)
This study evaluates the effectiveness of different doses of hormones (PMSG, HCG) at the time of occurrence, duration of oestrus and reproductive performance of the delayed oestrus civets. The experiment was conducted on 54 female civets and 42 male civets at Dong Nai Biotechnology Center and Thanh Long Wildlife Farm. PMSG/HCG product (Gestavet – UK) was administered intramuscularly in three formulations (CT), namely CT1: 20 IU PMSG + 10 IU HCG; CT2: 30 IU PMSG + 15 IU HCG; CT3: 40 IU PMSG + 20 IU HCG. The results show that the duration of oestrus averages from 1.1 days to 2.6 days after injecting sex hormones. CT3 had the earliest time of estrus. The duration of oestrus lasted from 2.9 to 3.9 days. The shortest estrous time was found at CT1 and the longest estrous time was at CT3 (p < 0.05). The ratio of oestrus and pregnancy increased compared with controls in all experimental civet groups. The average number of civets born on the litter ranges from 1.67 to 3.25 civets/litter; CT3 always had birth civets higher than that on the other formulas (p < 0.05). The average birth weight is from 94.02 to 97.25 g. Formulation CT3 could be applied effectively for the treatment on the first delays and delayed oestrus of the common palm civets.